2005
DOI: 10.1038/sj.jp.7211434
|View full text |Cite
|
Sign up to set email alerts
|

Hood versus mask nebulization in infants with evolving bronchopulmonary dysplasia in the neonatal intensive care unit

Abstract: Objective: To compare infants' discomfort, nursing-time and caregiver preference, and assess the clinical efficiency (as a secondary outcome) of hood versus facemask nebulization in infants with evolving bronchopulmonary dysplasia (BPD) in the neonatal intensive care unit. Study Design:A prospective, open, randomized, controlled crossover clinical trial. In total, 10 infants with BPD who were on inhaled betaagonist bronchodilators and corticosteroids were randomly assigned to receive their nebulized treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Infants' discomfort score was significantly lower for hood versus mask nebulization, and hood treatment could be less time-consuming for caregivers due to its easy operation. (5) Similar results were also reported by Bar-Yishay et al (6) in their pilot study that compared lung function response to bronchodilator nebulization via hood and mask. Numerical modeling and simulation of hood treatment include reports by Amirav et al (7) and Shakked et al, (8,9) who studied related issues such as the carrier airflow, lung delivery efficiency, and eye depositions.…”
Section: Introductionsupporting
confidence: 87%
“…Infants' discomfort score was significantly lower for hood versus mask nebulization, and hood treatment could be less time-consuming for caregivers due to its easy operation. (5) Similar results were also reported by Bar-Yishay et al (6) in their pilot study that compared lung function response to bronchodilator nebulization via hood and mask. Numerical modeling and simulation of hood treatment include reports by Amirav et al (7) and Shakked et al, (8,9) who studied related issues such as the carrier airflow, lung delivery efficiency, and eye depositions.…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, treatment time and discomfort were shown to be lower in infants with chronic lung disease using the hood. 43 In one study, 44 respiratory scores were not different in infants with bronchiolitis receiving bronchodilators via an infant hood or a face mask, and parents preferred the hood over the mask for their babies. A hood represents a feasible option in children who will not tolerate a mouthpiece or mask treatment.…”
Section: Interface Selectionmentioning
confidence: 99%
“…Thirteen articles were excluded during appraisal (4 duplicates, 3 did not focus on BPD, 3 did not evaluate inhaled medications, 2 were incomplete, and 1 evaluated inhaled medications other than bronchodilators, or ICS), leaving 22 articles included in the review ( Fig 1 ). Characteristics of the 22 included studies [ 17 38 ] can be found in Table 1 . Quality assessment of the data revealed an overall high risk for potential bias in the included studies as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Details pertaining to randomization (listed method or unclear), allocation concealment (listed method or unclear), double blinding (yes, no, or unclear), power calculation (yes or no) and reporting of exact point statistical methods (yes or no) were collected. Each study [ 17 38 ] was scored for three levels of potential bias (low, high, or unclear). A “no” answer in any category was scored as a high risk for potential bias, whereas one “unclear” with otherwise all “yes” answers was scored as an unclear risk of bias.…”
Section: Methodsmentioning
confidence: 99%